A quantitative framework to evaluate urban ecological resilience: broadening understanding through multi-attribute perspectives - Wang, Yongyang; Cai, Yanpeng; Xie, Yulei; Zhang, Pan; Chen, Lei (Frontiers in Ecology and Evolution, 2023)
Intensive human and economic activities in urban areas harmed local resources and ecology, negatively impacting ecological resilience. Improving ecological resilience enhances the resistance and recovery capability of the urban ecosystem from adverse external risks. However, the quantitative research on urban ecological resilience is still ambiguous. Many studies lack quantitative assessment methods from multiple perspectives. In this study, we build a comprehensive framework to assess urban ecological resilience from four regime attributes. The results showed that (1) the average urban ecological resilience value presented a trend of first declining and then rising, (2) the difference between the direction of considering and dealing with social and ecological relationships in the development process was proposed by a city, (3) the correlation between urbanization level and ecological resilience indicated that the urban ecological resilience was increased in the areas with low urbanization level and decreased sharply in the areas with high urbanization level. This study evaluated urban ecological resilience for 48 cities in China and provided a specific theoretical basis for decision-makers in urban planning and development strategies.